1990
DOI: 10.1038/clpt.1990.148
|View full text |Cite
|
Sign up to set email alerts
|

Flecainide excretion in human breast milk

Abstract: Healthy human volunteers who intended not to breast feed were placed on a regimen of 100 mg oral flecainide every 12 hours for 5 1/2 days beginning 1 day after parturition. Milk and blood samples were collected during the dosing period and for 2 days after the last dose. Concentrations of flecainide in milk and plasma were assayed by HPLC. Apparent steady-state levels of flecainide in both milk and plasma were achieved in most cases by day 4 of the study. Highest daily average concentration of flecainide in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…The RID is often used to evaluate the effect of maternal medication use on the breastfed infant, and an RID below 10% is considered safe (5). Two previous studies estimated the RID instead of ecainide quanti cation in neonatal blood and found proportions of 3.6% and 4.5% (3,4). Our RID was 5.6%, which is quite comparable with the previous studies.…”
Section: Discussion Conclusionsupporting
confidence: 85%
“…The RID is often used to evaluate the effect of maternal medication use on the breastfed infant, and an RID below 10% is considered safe (5). Two previous studies estimated the RID instead of ecainide quanti cation in neonatal blood and found proportions of 3.6% and 4.5% (3,4). Our RID was 5.6%, which is quite comparable with the previous studies.…”
Section: Discussion Conclusionsupporting
confidence: 85%
“…The m/p ratios for these drugs are presented in Table 1. 974 The empiric m/p ratio ranged from 0.005 (implying very scarce transfer into milk) and up to 5.7 (meaning that milk level was almost sixfold higher than in maternal blood).…”
Section: Published Data On M/p Ratio In the Literaturementioning
confidence: 99%
“…Table 2 9,1120,2232,3456,58,60,61,65,67,71 presents the 3 values included in Atkinson's predictions for which there were sufficient literature values. Table 3 920,2232,34…”
Section: The Atkinson Prediction Versus Experimental Datamentioning
confidence: 99%
“…2 Digoxin used by breast-feeding mothers results in undetectable infant serum concentrations (Table 3). [13][14][15][16][17][18][19][20][21][22][23][24][25][26]…”
Section: Antiarrhythmicsmentioning
confidence: 99%